Dividend Policy and Firm Performance: A Study of Listed Firms in Nigeria - Uwalomwa Uwuigbe; Jimoh Jafaru; Anijesushola Ajayi (Journal of Accounting and Management Information Systems (JAMIS), 2012)
This study basically investigates the relationship between the financial performance and dividend payout among listed firms' in Nigeria. It also looks at the relationship between ownership structure, size of firms and the dividend payouts. The annual reports for the period 2006-2010 were utilized as the main source of data collection for the 50 sampled firms. The regression analysis method was employed as a statistical technique for analysing the data collected. We find that there is a significant positive association between the performance of firms and the dividend payout of the sampled firms in Nigeria. The study also revealed that ownership structure and firm's size has a significant impact of the dividend payout of firms too.
Keywords: M41; 650; Financial performance; annual reports; firms; ownership structure; dividend policy; dividend payout; Nigeria